Putusan Hakim Terhadap Anak Yang Melakukan Tindak Pidana Pencurian Ditinjau Dari Undang Undang Nomor 17 Tahun 2016 Tentang Perlindungan Anak: (Studi Kasus Putusan Nomor 7/Pid.Sus-Anak/2020/PN Ksp) - Sarjanagori Siregar, Mahzaniar (Pusdikra Publishing, 2022)
This study aims to determine the analysis of judges' decisions regarding cases of theft of minors with the study of decision number 7/Pid.Sus-Anak/2020/PN Ksp, and to find out the judges' considerations in imposing criminal penalties on underage children in decision number 7 /Pid.Sus- Anak/2020/PN Ksp. In writing this thesis, it is normative legal research supported by empirical research data, meaning that this research was conducted by examining library materials or primary legal materials and secondary secondary legal materials. The results of this study indicate that, Decision number 7/Pid.Sus-Anak/2020/PN Ksp addresses some of the judges' considerations in imposing a criminal sentence for child defendants with a criminal form of coaching for 6 (six) months at the Kuala Simpang Penitentiary, with the first consideration The child's actions disturbed the community and the two defendants considered that they had committed the crime of theft.